A redefinição do conceito de classe e suas implicações políticas: uma análise sobre Ellen Meiksins Wood - Nascimento, Jefferson Ferreira do (2018)
The present dissertation examines the work of Ellen Meiksins Wood in order to understand: (1) how the conception of social class changes in the renewal of historical materialism presented by E. Wood; (2) how this change has repercussions on the analysis of the political role of the social class; (3) and how this change relates to the concept of Democracy thought by the author. The starting point is the author's observation that contemporary democracy cannot face class exploitation, since citizenship is not determined by socioeconomic status and civic equality in contemporary democracies does not impact class inequality. Thus, from the insights and suggestions elaborated by E. P. Thompson, the historian and political theorist Ellen Wood proposes to analyze the relevance of politics as an instrument of social domination and the place of specifically political conflicts in the processes of transition between the different modes of production and in overcoming class domination. Therefore, the proposal is to deepen the theoretical efforts to think class as relation and process and to increase the knowledge about the political role of the working class in the constitution of Substantive Democracy. The first result concerns the concept of class operated by E. Wood, who sees a theoretical advance in the proposition of E. P. Thompson. This leads us to the second result: class conception is related to a specific historical context. In “certain historical conditions, class situations generate class formations.” It is experience, as an effect of objective determinations – relations of production and class exploitation – which brings together heterogeneous groups. This understanding results in a new possibility to reflect the working class in times of flexible accumulation and theories that support fragmentary analyzes of the world. The third result is that we live in a formal democracy where free labor is dominant, but it is exalted from an ideology that justifies the subjection of the worker to capitalist disciplines. With the separation of the civic condition from the class situation, the civil liberty of the worker is neutralized by the economic pressures of capitalism. For instance, class equality is something very different from ethnic or gender equality, since, in some sense, formal equality can be extended to different ethnic or gender groups without threatening the capitalist system – the same cannot be said in relation to class equality. Thus, respecting the plurality of human experience cannot mean “the dissolution of historical causality”.